Cytotoxic Prenyl and Geranyl Coumarins from the Stem Bark of Casimiroa edulis - Tun, Khun N. W.; Aminah, Nanik S.; Kristanti, Alfinda Novi; Ramadhan, Rico; Takaya, Yoshiaki (Letters in Organic Chemistry, 2020)
Phytochemical investigation of the methanolic extract of the stem bark of Casimiroa edulis afforded four coumarins. Various spectroscopic experiments were used to characterize the isolated coumarins. The structures were identified as auraptene (K-1), suberosin (K-2), 5-geranyloxypsoralen (bergamottin) (K-3), and 8-geranyloxypsoralen (K-4), based on the chemical and spectral analysis. Among these compounds, suberosin (K-2) and 5-geranyloxypsoralen (bergamottin) (K-3) were isolated for the first time from this genus, and auraptene (K-1) was isolated from this plant for the first time. Cytotoxicity of pure compound K-4 and sub-fraction MD-3 was evaluated against HeLa and T47D cell lines and moderate activity was found with an IC50 value in the range 17.4 to 72.33 μg/mL.
Keywords: HeLa